2018
DOI: 10.20517/2574-1209.2018.23
|View full text |Cite
|
Sign up to set email alerts
|

The endothelial progenitor cell dysfunction in hypertension: the diagnostic and predictive values

Abstract: Hypertension remains a leading risk factor of cardiovascular (CV) events and disease in the general population. The prevalence of hypertension is present in developed and developing countries and according to various assessments may fluctuate between 30% to 90% with considerable regional differences. Hypertension influences CV risk and mortality rate through target organ damages that affect vasculature particularly endothelium. Endothelial dysfunction is an independent risk factor of CV complications. Recent s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 82 publications
(108 reference statements)
0
7
0
Order By: Relevance
“…EPC and ECFC are endothelial precursor cells originating from the bone marrow stem cells and human umbilical cord blood. Upon maturation, they become mature endothelial cells and release pro-angiogenic factors like VEGF and placental growth factor (PlGF), which enhance vasculogenesis and endothelial repair ( 52 ). Studies found that the numbers of EPC and ECFC in the offspring of preeclampsia mothers were reduced ( 23 , 24 ), and the EPC were also found to be more senescent, consequently reducing their functional ability ( 53 , 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…EPC and ECFC are endothelial precursor cells originating from the bone marrow stem cells and human umbilical cord blood. Upon maturation, they become mature endothelial cells and release pro-angiogenic factors like VEGF and placental growth factor (PlGF), which enhance vasculogenesis and endothelial repair ( 52 ). Studies found that the numbers of EPC and ECFC in the offspring of preeclampsia mothers were reduced ( 23 , 24 ), and the EPC were also found to be more senescent, consequently reducing their functional ability ( 53 , 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…VEGF has been known as a signalling protein produced by cells to stimulate vasculoand angiogenesis, induced by hypoxia and possesses the properties of endothelial cell mitogen, which promotes survival of endothelial cells, and stimulates the production of a powerful vasodilator, nitric oxide (NO), associated with gestational vessel dilation characteristic of normal pregnancy [5,6]. CD32 + CD40 + CEM has been shown to act as a marker of endothelial damage, and changes in its level point out increased ED progression in pathological conditions or the possibility of its renewal [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…There is a large body of evidence regarding the pivotal role of EPCs in developing cardiovascular (CV) diseases and CV events [3][4][5][6]. For instance, nature evolution of vast range of CV diseases were associated with deficiency of circulating number of EPCs as well as weak function of endothelial precursors including mobbing, proliferation, differentiation and survival, which were incorporated into term EPC dysfunction [7]. In patients with pre-hypertension and hypertension lowered number and declined function of EPCs were identified and EPC dysfunction appeared to be a biomarker of endothelial dysfunction and arterial stiffness [8].…”
Section: Introductionmentioning
confidence: 99%
“…There are wide ranges of stimuli that are candidates for co-regulators of epigenetic influences and receptor-targeting effectors result in both decreasing number of EPCs in peripheral blood and weak their function, i.e. inflammatory cytokines, increased fasting glucose, hyperinsulinemia, components of oxidative stress such as oxidized low-density protein cholesterol, galectines, free radicals, as well as growth factors (growth factor-bets), catecholamines, and hormones (renin, angiotensin-II, aldosterone, endothelin-1) [4,7,10]. Unfortunately, all these findings do not explain why some patients without CV risk factors demonstrate EPC dysfunction before hypertension manifestation.…”
Section: Introductionmentioning
confidence: 99%